Differences in morphological and physiological plasticity in two species of first-year conifer seedlings exposed to drought result in distinct survivorship patterns. (10th June 2019) - Augustine, Steven P; Reinhardt, Keith
Abstract: First-year tree seedlings represent a critical demographic life stage, functioning as a bottleneck to forest regeneration. Knowledge of how mortality is related to whole-seedling carbon and water relations is deficient and is required to understand how forest compositions will be altered in future climatic conditions. We performed a greenhouse drought experiment using first-year seedlings of two common pine species found in the Intermountain West, USA. Gas exchange, biomass gain, allometry and xylem water potentials were compared between well-watered and droughted seedlings from emergence until drought-induced mortality. In both species, morphological adjustments to confer drought tolerance, such as increased leaf mass per unit area, were not observed in seedlings exposed to drought, and droughted seedlings maintained photosynthesis and whole-seedling carbon gain well into the experiment. Yet, there were important differences between species in terms of carbon budgets, physiological responses and mortality patterns. In Pinus ponderosa P. & C. Lawson, physiological acclimation to drought was much greater, evident through stronger stomatal regulation and increased water-use efficiency. Photosynthesis and carbon budgets in P. ponderosa were greater than in Pinus contorta Dougl. ex. Loud., and survival was 100% until critical hydraulic thresholds in leaf water content and seedling water potentials were crossed. In P. contorta, physiological adjustments to drought were less, and mortality occurred much sooner and well before injurious hydraulic thresholds were approached. First-year conifer seedlings appear canalized for a suite of functional traits that prioritize short-term carbon gain over long-term drought tolerance, suggesting that conifer seedling survival is linked with carbon limitations, even during drought, with survival in species having narrower carbon survival margins being more hampered by carbon limitations.